The Influence of Differentiation Learning Strategies on Students' Creative Thinking Skills in History Learning at Senior High School - Maulidan, Aldi Cahya (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This research is motivated by the fact that history education has so far provided little room for students to develop creativity based on their interests and talents. This issue arises because learning places greater emphasis on memorisation, whereas differentiated learning allows lessons to be tailored according to students’ interests and talents, enabling them to produce work that aligns with their competencies. This study employs a quantitative research method with a quasi-experimental approach. Quasi-experimental methods in educational research are used to determine the effect of independent variables on dependent variables. This research involves two classes as the subjects of study at SHS 5 Tasikmalaya. Data collection in this study is conducted through tests to measure students’ competence. The collected data is then analysed through the stages of normality testing, homogeneity testing, hypothesis testing, and the N-Gain test. The findings indicate that differentiated learning has an impact on students' creative thinking skills in history education. Differentiated learning reinforces the idea that all students have equal opportunities to create and innovate throughout the learning process. Its objective is to foster an inclusive learning environment to maximise each student’s potential.